EFFECTIVENESS OF TWO STAY TWO STRAY LEARNING METHODS AT ISLAMIC EDUCATION (PAI) SUBJECTS TO IMPROVE LEARNING OUTCOMES OF STUDENTS OF SMK DWI PUTRI HUSADA, BOGOR CITY - Ridwan Hadi Pratama; Hidayah Baisa (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
This research is a classroom action research, conducted collaboratively between researchers and collaborators. The purpose of this study was to improve the learning outcomes of Islamic Education (PAI) subjects in class X students using Two Stay Two Stray Learning Method (TSTS). The object of this research was students of the SMK Dwi Putri Husada in Bogor City consisting of 43 students. This research was conducted in the odd semester of the academic year 2017/2018. The results showed that the average value of PAI subjects in the first cycle obtained mastery learning outcomes of 44.19%, learning outcomes in the second cycle obtained completeness of learning outcomes by 86.04%. While in the third cycle obtained the completeness of learning outcomes of 91.4 %. the quality of learning implementation in the first cycle obtained a value of 69 and in the second cycle increased to 81. And in the third cycle increased to 90. Based on the results of the study it can be concluded that the Two Stay Two Stray learning method can improve student learning outcomes in class X in SMK Dwi Putri Husada, Bogor City. In addition, the Two Stay Two Stray learning method can increase the activity, cooperation, and courage of students in the learning process.